Lowokwaru People's Perception on The Marriage Agreement (The Implementation of Article 29 of The Marriage Law Based on Legal System Theory) - Nasyiah, Iffaty; Rahmania, Faiza; Jamilah, Jamilah (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 3 (2023): The 6th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2023)
This study aims to analyze the perception of the people of Lowokwaru to the marriage agreement stipulated in Article 29 of the law on marriage. Although the marriage agreement has been regulated both in substance and procedure, but very few people who make a marriage agreement especially regarding the separation of property. This study is a juridical-empirical research with sociological juridical approach. The data used are qualitative data collected through semi-structural interview techniques. To obtain field data, 15 people were involved as a sample, which included married and pre-married couples, as well as the head of the Religious Affairs Office. The theory used in the analysis is the theory of Lawrence m's legal system. Friedman. The results of the study are: 1). The majority of respondents considered the marriage agreement unnecessary because the marriage is done for life; 2). In its implementation, only a few people enter into marriage agreements (only 2 agreements in 2022) with the procedure established by law; 3). according to Lawrence M. Friedman, in the substance of the law there is no problem, in terms of legal structure, the relevant officials have carried out the procedures as stipulated in the legislation. In legal culture, some people still consider it taboo, unethical, materialistic so that there is no need for a marriage agreement.